2022
DOI: 10.1021/acs.jcim.2c00539
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the Enamine and Imine Forms of the Hydrolyzed Imipenem in the Active Sites of Metallo-β-lactamases and in Water Solution

Abstract: Deactivation of the β-lactam antibiotics in the active sites of the β-lactamases is among the main mechanisms of bacterial antibiotic resistance. As drugs of last resort, carbapenems are efficiently hydrolyzed by metallo-β-lactamases, presenting a serious threat to human health. Our study reveals mechanistic aspects of the imipenem hydrolysis by bizinc metallo-β-lactamases, NDM-1 and L1, belonging to the B1 and the B3 subclasses, respectively. The results of QM­(PBE0-D3/6-31G**)/MM simulations show that the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…This is in line with the analysis of the ES complex: the carbonyl carbon atom of the substrate is more electrophilic due to the tighter and less flexible binding of the imipenem in the L1 active site. These results are in line with the data obtained on potential energy surface [ 8 ]. The energy barrier is lower, and the intermediate stabilization energy is larger in the L1 compared with the NDM-1.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This is in line with the analysis of the ES complex: the carbonyl carbon atom of the substrate is more electrophilic due to the tighter and less flexible binding of the imipenem in the L1 active site. These results are in line with the data obtained on potential energy surface [ 8 ]. The energy barrier is lower, and the intermediate stabilization energy is larger in the L1 compared with the NDM-1.…”
Section: Resultssupporting
confidence: 92%
“…Machine learning reveals that all geometry parameters, including distance of the nucleophilic attack, coordination bond lengths between the substrate and zinc cations, and C=O and C–N covalent bond lengths in the active site have similar importance for the Fukui index estimates. Gibbs energy profiles calculated for the hydrolysis of the imipenem in the active sites of the L1 and NDM-1 shares the same features with the profiles on the potential energy surface [ 8 ]. Formation of tighter and more rigid active site in the L1 leads to the lower energy barrier and larger extent of the intermediate stabilization relative to the ES complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our data therefore support the accumulation of the carbapenem-derived ( S )-Δ 1 -imine on the active site, as previously suggested ( 22 ), two possible explanations for this exclusive observation present themselves: either the Δ 2 -enamine product rapidly leaves the L1 active site, tautomerizes in solution to the (thermodynamically favored) ( S )-Δ 1 -imine and then rebinds or the ( S )-Δ 1 -imine slowly accumulates in the active site, leaving more slowly than other tautomeric forms/stereoisomers (whose initial production may be preferred kinetically) due to the increased stability of the L1 complex. Recent QM/MM studies ( 61 ) on the L1 reaction pathway suggest that C-2 protonation of an imipenem-derived anionic intermediate was blocked at the active site by Pro227 on the L10 loop ( Fig. S2 ).…”
Section: Discussionmentioning
confidence: 94%
“…Krivitskaya and Khrenova used QM/MM approaches to compare mechanistic aspects of imipenem hydrolysis by two important metallo-β-lactamases, namely, NDM-1 and L1 . It was demonstrated that, although the two enzymes share a similar substrate range, they exhibit distinct reaction pathways with the formation of different reaction products.…”
mentioning
confidence: 99%